2023
DOI: 10.1097/jhq.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

What are Effective Strategies to Reduce Low-Value Care? An Analysis of 121 Randomized Deimplementation Studies

Pauline Heus,
Simone A. van Dulmen,
Jan-Willem Weenink
et al.

Abstract: Background: Low-value care is healthcare leading to no or little clinical benefit for the patient. The best (combinations of) interventions to reduce low-value care are unclear. Purpose: To provide an overview of randomized controlled trials (RCTs) evaluating deimplementation strategies, to quantify the effectiveness and describe different combinations of strategies. Methods: Analysis of 121 RCTs (1990–2019)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This notion could provide an explanation as to why we observed that in case of opioids (almost) no change in prescription rates was observed, while the rates of the other types of care did show to change (and the number and distribution of patients remained the same over the period examined). Furthermore, the observation that the COVID-19 restrictions differentially affected low-value GP care provision supports the idea that deïmplementation of low-value care requires tailored interventions [ 55 , 56 ]. A recently published review showed that among the existing studies examining the impact of deïmplementation strategies showed that strategies targeting healthcare providers, patients or organizational context are often more effective [ 55 ].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This notion could provide an explanation as to why we observed that in case of opioids (almost) no change in prescription rates was observed, while the rates of the other types of care did show to change (and the number and distribution of patients remained the same over the period examined). Furthermore, the observation that the COVID-19 restrictions differentially affected low-value GP care provision supports the idea that deïmplementation of low-value care requires tailored interventions [ 55 , 56 ]. A recently published review showed that among the existing studies examining the impact of deïmplementation strategies showed that strategies targeting healthcare providers, patients or organizational context are often more effective [ 55 ].…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, the observation that the COVID-19 restrictions differentially affected low-value GP care provision supports the idea that deïmplementation of low-value care requires tailored interventions [ 55 , 56 ]. A recently published review showed that among the existing studies examining the impact of deïmplementation strategies showed that strategies targeting healthcare providers, patients or organizational context are often more effective [ 55 ]. Suggesting that the provision of low-value care is often the result of an interplay of factors existing on multiple levels.…”
Section: Discussionmentioning
confidence: 68%
“…The use of abdominal and pelvic drain(s) will continue to exist in a minority (for example, <20 per cent) of selected patients (low rectal anastomoses, immunocompromised and/or frail patients, heavily contaminated or dirty procedures, excessive blood loss and/or intraoperative complications). However, the routine placement is not supported 43 , and a progressive de-implementation strategy should be actively sought at organizational and surgeon levels 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Heus et al recently published a review exploring 121 randomised clinical trials evaluating various deimplementation strategies. 16 While the authors report that 'Most deimplementation strategies achieved a considerable reduction of low-value care', they also note that they 'found no signs that a particular type or number of interventions works best for deimplementation'.…”
Section: What This Study Addsmentioning
confidence: 99%
“…All these tools have a common trait—they are based on the assumption that knowledge of areas of unwarranted variation in healthcare automatically will lead to a reduction in unwarranted variation—and recommendations regarding how to reduce this variation are not very prominent. Heus et al recently published a review exploring 121 randomised clinical trials evaluating various deimplementation strategies 16. While the authors report that ‘Most deimplementation strategies achieved a considerable reduction of low-value care’, they also note that they ‘found no signs that a particular type or number of interventions works best for deimplementation’.…”
Section: Introductionmentioning
confidence: 99%